PENGEMBANGAN PRODUK LAMPU MEJA BELAJAR DENGAN METODE KANO DAN QUALITY FUNCTION DEPLOYMENT (QFD) - Aji, Edy Rustam; Yuliawati, Evi (Journal of Research and Technology, 2016)
The demand for students, college students or office workers to do their study and work require them to sit longer in their study or work place. The place of study must be designed in order to be comfortable, ergonomic, and has aesthetics touches. Study lamp is one of important aspects in study place. Study lamp design has improved in its aspects and function. However, along with its improvement, there are demands of additional function to the existing designs. On that account, this research aims to design and produce the desk lamp with additional functions according to users’ requirement. To realize this aim, Kano and Quality Function Deployment (QFD) methods are applied. The calculation result showed 12 attributes (customer requirements) and 10 technical parameter priorities were implemented in the design of desk lamp product.  The  additional  functions of  this  desk  lamp  are alternating automatic power off between the desk lamp and night lamp whenever one of the lamp not in use, flip design, digital clock, fan, night lamp, cellular phone charger, stationary case, and ability to stay on during the electricity black out.